楚科奇海与加拿大海盆表层沉积物表观特征及其环境指示 - 高爱国; 王汝建; 陈建芳; 张德玉; 张道建 (2008)
通过对中国首次和第二次北极科学考察采集的表层沉积物的观察,根据沉积物的颜色和气味、砾石分布、底栖生物及贝壳分布特征的分析,探讨了该海区表层沉积物表观特征变化与有机质输入、沉积物的氧化还原状态的关系、底栖生物分布范围、冰筏碎屑的分布区域及与海流的关系,指出在研究区软体动物生长的北界位于73.5°N,比浮游动物的北界约低2个纬度。冰筏碎屑的北界可作为融冰水的北界或永久冰区的南界,位置在77°24′N附近。通过对沉积物表观特征的综合分析,结合研究区的海流特征,指出研究区的海流分布对沉积物分布有重要影响,尤其是两股不同性质的海流相遇,对西南部与东部两个区域的沉积物组成及性质具有较强的控制作用。 The apparent features of surface sediments collected during Chinese First and Second Arctic Research Expedition were observed.Based on the recognition of color and odor of the sediments,distribution of gravels or ice-rafted debris and molluscan remains in the surface sediments,we discuss the relation among the apparent features of surface sediments and the content of organic matters,oxidation-reduction status as well as the distribution range of benthos,ice-rafted detritus and the relation with ocean current.We find that the north boundary of mollusks is located at 73.5°N,which is 2° lower than that of zooplanktons.The north boundary of ice-rafted detritus which is also the north boundary of melting water and equals to the south boundary of permanent ice region,appears near 77°24'N.According to analysis of apparent features of sediments,combining with current characteristics in study area,we conclude that current plays an important role in distribution of sediments,especially for that within the southwest region and east region. 国家自然科学基金项目(40576060,40376017)